Assessment of the Correlation between Energy Rating Labeling Regulations and Performance Metrics for Residential Air Conditioning Units: Case Study Variable Type Air Conditioners - Andrade, Angel; Zapata-Mina, Juan; Restrepo, Alvaro (International Journal of Energy Economics and Policy, 2023)
To comply with the Paris Agreement, many countries have implemented mandatory energy certification policies in the HVAC sector. These policies have encouraged the deployment of more energy efficient technologies such as variable or inverter driven technologies, which have been developed based on established seasonal performance metrics. Therefore, this paper presents an experimental evaluation of a variable-type air conditioner based on seasonal cooling metrics and performance ratings using various energy labeling programs from multiple regions around the world. The results of this work demonstrate that the energy efficiency rating of an air conditioner is significantly influenced by the distribution of the reference outdoor temperature in the labeling program issued by each region, and not just by the adoption of a technical standard. These results are crucial for the development of public policies aimed at designing better energy efficiency and labeling programs. In particular, the findings are especially relevant for decision making by governments, as the adoption of a technical standard can be simplified, and greater harmonization of performance metrics used globally can lead to greater energy savings and mitigate the effects of global warming.